Eco-friendly management of postharvest fungal decays in kiwifruit. Issue 30 (7th November 2022) - Dai, Yuan; Wang, Zhenshuo; Leng, Jinsong; Sui, Yuan; Jiang, Mingguo; Wisniewski, Michael; Liu, Jia; Wang, Qi
Abstract: Kiwifruit is purchased by consumers worldwide and is increasing in demand. Unfortunately, kiwifruit is susceptible to postharvest decay caused by a variety of fungal pathogens, including Botrytis cinerea, Penicillium expansum, Alternaria alternata, Botryosphaeria dothidea, and Diaporthe spp. Among these pathogens, B. cinerea is the most prevalent and devastating. Infections by these fungal pathogens result in a deterioration in fruit quality and a reduction in marketable yield. Eco-friendly methods to control kiwifruit postharvest decay have been explored as alternatives to the use of synthetic fungicides. In this review, we provide an overview and discuss the virulence and pathogenesis of fungi that are causal agents of kiwifruit decay, especially B. cinerea, including recent molecular and genomic studies. Advances in pre- and postharvest measures for postharvest decay management, including biological control, physical applications, the use of natural compounds and plant hormones, and the use of combined methods, are also reviewed. Eco-friendly control measures are a critical component of an integrated management approach for sustainable production of kiwifruit. The need for further research on the use of microbial consortia for the management of postharvest diseases of kiwifruit is also discussed.